Effects of Polarity on the Filler-Rubber Interaction and Properties of Silica Filled Grafted Natural Rubber Composites. (27th October 2013) - Arayapranee, Wanvimon; Rempel, Garry L.
Abstract : The grafting of an olefinic monomer like acrylonitrile (AN), methyl methacrylate (MMA), and styrene (ST) onto natural rubber (NR) was carried out to enhance the polarity of the new chemical groups on the NR backbone and, in turn, to improve the filler-rubber interaction. The grafted natural rubber (GNR) produced was compounded and then vulcanization was carried out in the presence of silica as a reinforcing filler. The physical properties and aging resistance provided by the presence of the polar functional groups of the GNR composites were investigated and compared with other rubbers such as SBR, NBR, and NR. The GNRs provided significant improvements in resistance of the composites to thermal, oil, and ozone while maintaining the mechanical properties of the rubber. Therefore, these properties can be controlled as a function of the polarity of functional groups on the NR backbone. Morphological studies confirmed a shift from ductility failure to brittle with the presence of the polar group on the rubber chains.